Maltrato Familiar - Aguisa Yasig, Mercy Paulina (2017)
The present project seeks to determine the incidence of family abuse in the children´s academic performance of the 12 de Octubre Educational Unit. A situational diagnosis was made to know about family abuse in children and how it affects their educational environment. In addition, the used methodology was the bibliographic review and the application of surveys that allow obtaining real information of the raised problem. The research contributions added to the fact that teachers can identify the causes of low school performance and the effects of abuse in children. Furthermore, the direct beneficiaries are the children because they can receive help from the teacher or professional to guide in the solution of problems. Moreover, the obtained results showed that fifth year primary school children are badly treated for low grades and their low grades are because the teacher does not use an adequate methodology that maintains the interest in the learning process but not in the family abuse.